Children's Facial Emotional Expressions to Gender-Nonconforming Hypothetical Peers. - Kwan, Karen Man Wa; Isani, Simran; James, Haley J.; Nabbijohn, A. Natisha; MacMullin, Laura N.; Shi, Sylvia Yun; Poon, Bill Hung Piu; Peragine, Diana E.; Wong, Wang Ivy; VanderLaan, Doug P. (Archives of Sexual Behavior, 2025)
Prior studies suggested that children's appraisals of gender-nonconforming, compared with gender-conforming, peers are less positive, particularly for gender-nonconforming boys. To gauge appraisals, most prior studies used verbal reports, which provide explicit measures. In contrast, the current study explored facial emotional expressions, which can potentially be an objective and implicit measure to inform the emotional component of appraisals. We examined 4-, 5-, 8-, and 9-year-olds in Hong Kong (n = 309) and Canada (n = 296) (N = 605; 303 boys, 302 girls). Children's faces were video-recorded while viewing four vignettes of hypothetical gender-conforming and gender-nonconforming boy and girl targets in random order. Targets were shown as having gendered preferences in the domains of toys, activities, clothing and hairstyle, and playmates. FaceReader software was used to perform automated coding of six basic facial emotional expressions: angry, disgusted, happy, sad, scared, and surprised. Children showed more scared emotion toward the hypothetical gender-nonconforming boy target when compared with the gender-conforming boy target. Also, this elevation in scared emotion was correlated with children verbally reporting that they perceived the gender-nonconforming boy as being less happy relative to the gender-conforming boy. These results suggest that, during a brief initial exposure to a target peer, gender nonconformity in boy peers was related to a relatively heightened fear response in early and middle childhood. Further, facial emotional expressions can be used to gain insights regarding the emotional component of children's appraisals of varying peer gender presentations, and these emotional responses can be associated with certain other aspects of their appraisals.